A Software-Defined Radio System for Intravehicular Wireless Sensor Networks - Xiangming Kong; Deying Zhang; Mohin Ahmed (International Journal of Digital Multimedia Broadcasting)
An intra-vehicular wireless sensor network is designed and implemented on a software-defined radio system. IUWB signal is chosen to carry the data packets. The MAC layer of the system follows the specification of the IEEE802.15.4 standard. The transceiver design, especially the receiver design, is detailed in the paper. The system design is validated through lab test setup.